Mass spectrometry imaging identifies metabolic patterns associated with malignant potential in pheochromocytoma and paraganglioma. Issue 1 (5th June 2021) - Murakami, Masanori; Sun, Na; Greunke, Christian; Feuchtinger, Annette; Kircher, Stefan; Deutschbein, Timo; Papathomas, Thomas; Bechmann, Nicole; William Wallace, Paal; Peitzsch, Mirko; Korpershoek, Esther; Friemel, Juliane; et al.
Abstract : Objective: Within the past decade, important genetic drivers of pheochromocytoma and paraganglioma (PPGLs) development have been identified. The pathophysiological mechanism that translates these alterations into functional autonomy and potentially malignant behavior has not been elucidated in detail. Here we used MALDI-mass spectrometry imaging (MALDI-MSI) of formalin-fixed paraffin-embedded tissue specimens to comprehensively characterize the metabolic profiles of PPGLs. Design and methods: MALDI-MSI was conducted in 344 PPGLs and results correlated with genetic and phenotypic information. We experimentally silenced genetic drivers by siRNA in PC12 cells to confirm their metabolic impact in vitro . Results: Tissue abundance of kynurenine pathway metabolites such as xanthurenic acid was significantly lower ( P = 2.35E−09) in the pseudohypoxia pathway cluster 1 compared to PPGLs of the kinase-driven PPGLs cluster 2. Lower abundance of xanthurenic acid was associated with shorter metastasis-free survival (log-rank tests P = 7.96E−06) and identified as a risk factor for metastasis independent of the genetic status (hazard ratio, 32.6, P = 0.002). Knockdown of Sdhb and Vhl in an in vitro model demonstrated that inositol metabolism and sialic acids were similarly modulated as in tumors of the respective cluster. Conclusions: The present study has identified distinct tissue metabolomic profiles of PPGLs in relation to tumor genotypes. In addition, we revealed significantly altered metabolites in the kynurenine pathway in metastatic PPGLs, which can aid in the prediction of its malignant potential. However, further validation studies will be required to confirm our findings.